Influence of Applied Nitrogen on Soil Water, Soil Nitrate (NO3-) Concentration and Crop Yields in a Potato Field in the Saïs Plain - Chaimae Nessah; Abdellah El Hmaidi; Abdelhakim Lahjouj; El Mati El Faleh; Aissa Masrour; Karima Bouhafa (European Scientific Journal, ESJ, 2026)
Nitrate (NO₃⁻) leaching is a growing global environmental concern, particularly in intensively cultivated regions. The Saïss Plain, a major agricultural area in Morocco, has experienced increased nonpoint-source pollution due to excessive nitrogen (N) fertilizer use. A field experiment was conducted at the Douyet experimental station to assess the short-term effects of different N application rates on soil water content (SWC), soil nitrate (NO₃–N) dynamics, and potato (Solanum tuberosum L.) tuber yield within the 0–100 cm soil profile under irrigated conditions during the 2021 and 2022 growing seasons. The experiment was arranged in a randomized complete block design with three replications and six N fertilizer rates (0, 90, 135, 180, 225, and 275 kg N ha⁻¹). Soil samples were collected from five depth intervals (0–20, 20–40, 40–60, 60–80, and 80–100 cm). Nitrogen rates did not significantly affect SWC at any soil depth in either season. However, soil water dynamics were strongly influenced by irrigation, particularly in the 0–20 cm layer, where SWC decreased before irrigation and increased significantly afterward. In 2021, only slight temporal variations in soil NO₃–N concentrations were observed among N treatments. In contrast, in 2022, NO₃–N distribution across the 0–100 cm profile showed notable month-to-month variability, with higher nitrate levels occurring at specific crop growth stages depending on N rates. Nitrogen application rates significantly influenced potato tuber yield. These results suggest that optimizing N supply to match crop demand, adopting split N applications, and improving irrigation management (e.g., drip irrigation and uniform water distribution) can enhance potato productivity while reducing nitrate accumulation and potential leaching risks.